Short Observation Period and Aggressive Discharge of Patients With Head Injury and Serial CT Scans. Issue 5 (May 2023) - Perkins, Jordan; Shreffler, Jacob; Kamenec, Danielle; Bequer, Alexandra; Ziemba, Corey; O'Brien, Dan; Shoff, Hugh; Smith, Jason; Nash, Nicholas; Huecker, Martin
Background: Many patients undergo two head computed tomography (CT) scans after mild traumatic brain injury (TBI). Radiographic progression without clinical deterioration does not usually alter management. Evidence-based guidelines offer potential for limited repeat imaging and safe discharge. This study characterizes patients who had two head CTs in the Emergency Department (ED), determines the change between initial and repeat CTs, and describes timing of repeat scans. Methods: This retrospective series includes all patients with head CTs during the same ED visit at an urban trauma center between May 1st, 2016 and April 30th, 2018. Radiographic interpretation was coded as positive, negative, or equivocal. Results: Of 241 subjects, the number of positive, negative, and equivocal initial CT results were 154, 50, and 37, respectively. On repeat CT, 190 (78.8%) interpretations were congruent with the original scan. Out of the 21.2% of repeat scans that diverged from the original read, 14 (5.8%) showed positive to negative conversion, 1 (.4%) showed positive to equivocal conversion, 2 (.88%) showed negative to positive conversion, 20 (8.3%) showed equivocal to negative conversion, and 14 (5.8%) showed equivocal to positive conversion. Average time between scans was 4.4 hours, and median length of stay was 10.2 hours. Conclusions: In this retrospective review, most repeat CT scans had no new findings. A small percentage converted to positive, rarely altering clinical management. This study demonstrates the need for continued prospective research to update clinical guidelines that could reduce admission and serial CT scanning for mild TBI.